Murine junctional adhesion molecules JAM-B and JAM-C mediate endothelial and stellate cell interactions during hepatic fibrosis. Issue 4 (3rd July 2016) - Hintermann, Edith; Bayer, Monika; Ehser, Janine; Aurrand-Lions, Michel; Pfeilschifter, Josef M.; Imhof, Beat A.; Christen, Urs
ABSTRACT: Classical junctional adhesion molecules JAM-A, JAM-B and JAM-C influence vascular permeability, cell polarity as well as leukocyte recruitment and immigration into inflamed tissue. As the vasculature becomes remodelled in chronically injured, fibrotic livers we aimed to determine distribution and role of junctional adhesion molecules during this pathological process. Therefore, livers of naïve or carbon tetrachloride-treated mice were analyzed by immunohistochemistry to localize all 3 classical junctional adhesion molecules. Hepatic stellate cells and endothelial cells were isolated and subjected to immunocytochemistry and flow cytometry to determine localization and functionality of JAM-B and JAM-C. Cells were further used to perform contractility and migration assays and to study endothelial tubulogenesis and pericytic coverage by hepatic stellate cells. We found that in healthy tissue, JAM-A was ubiquitously expressed whereas JAM-B and JAM-C were restricted to the vasculature. During fibrosis, JAM-B and JAM-C levels increased in endothelial cells and JAM-C was de novo generated in myofibroblastic hepatic stellate cells. Soluble JAM-C blocked contractility but increased motility in hepatic stellate cells. Furthermore, soluble JAM-C reduced endothelial tubulogenesis and endothelial cell/stellate cell interaction. Thus, during liver fibrogenesis, JAM-B and JAM-C expression increase on the vascular endothelium. More importantly, JAM-C appears on myofibroblastic hepatic stellate cells linking them as pericytes to JAM-B positive endothelial cells. This JAM-B/JAM-C mediated interaction between endothelial cells and stellate cells stabilizes vessel walls and may control the sinusoidal diameter. Increased hepatic stellate cell contraction mediated by JAM-C/JAM-C interaction may cause intrahepatic vasoconstriction, which is a major complication in liver cirrhosis.